Contextualizando os conceitos de átomo e elemento químico a partir da leitura de rótulo/embalagens - CHAVES, Jamille Palheta Rodrigues (2023)
This Course Conclusion Work has a format that meets the prerequisites of Normative Instruction No. 01/2023 - PROEG/UFPA and is in accordance with Art. 4, items II and IV, which provides, on an exceptional and temporary basis, on the academic guidelines for the standardization and performance of the activities of the Course Conclusion Work - TCC, making its form of defense more flexible, due to the consequences of the COVID -19 pandemic. Held at EEEFM. Luiz Nunes Direto, in the municipality of Ananindeua-PA. The extension practice was planned and organized as part of the curricular activity Pedagogical Practices in Chemistry IV, of the Chemistry Degree course at the University Campus of Ananindeua - PA. The aim is to understand the concept of atoms and the definition of a chemical element, which are fundamental concepts for understanding the properties of the different materials present in everyday life. The atomic structure and the definition of a chemical element were contextualized by reading the labels of foods consumed daily by teenagers during an interactive exhibition with the aim of arousing the students' interest in understanding the indications of chemical elements present in the products. Even though these conceptualizations are difficult to assimilate due to their high degree of abstraction, our results indicate that this contextualization strategy made it possible to gain a better understanding of the objects of study and was perceived by the students as facilitating their learning.